Pengembangan Media Digital Untuk Informasi Warga Gereja - Saragih, Saut Pintubipar (Prosiding, 2024)
The church news that is currently used is a media that is distributed to all church members on certain days only, namely Sundays. The needs of church members for the latest information and also in accelerating the process of managing documentation and giving donations or tithes to the church are also not available other than on Sundays. This study was conducted using the basis of the problems that have been reviewed by the researcher. Data collected from the church in the form of church news formats, forms that must be filled in by the congregation prove that there is no flexibility in the process or work system of disseminating information in the church. This study was conducted using the information system development method, namely waterfall. In the initial analysis, a SWOT analysis was also used to see how the system conditions occurred and then describe the flow of the system in an information system flow. Development was carried out using development tools such as unified modeling languages, programming languages, and other design tools as needed. The results of the study obtained were a system that could provide a media system in digital form or internet-based media that would be available at any time to all system users in the church. The results of this study provide features according to the needs of church members, such as church news features, congregation databases, donation or tithe features, and weekly news features.